2011
DOI: 10.1515/ijdhd.2011.032
|View full text |Cite
|
Sign up to set email alerts
|

Chinese migrant children’s mental health and career efficacy: the roles of mentoring relationship quality and self-efficacy

Abstract: The current study aimed to examine whether migrant children ' s relationship quality with mentors could make unique contributions in predicting their mental health and career effi cacy, above and beyond the prediction from their relationship quality with parents. Based on social cognitive theory, it was also proposed that migrant children ' s self-effi cacy beliefs may mediate the positive effects of mentoring relationship quality on career effi cacy and mental health. A survey study was conducted among Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Mentors’ rated support was also related to an increase in empathy, cooperation, self-control, assertiveness [ 49 ], social self-efficacy, and sense of community [ 50 ]. Mentees’ rated feelings of trust and closeness with their mentors were positively associated with an increase in social support and family bonding, scholastic competence, feelings of self-worth [ 18 , 51 , 52 , 53 , 54 ], self-regulation [ 55 ], hope, self-esteem, self-efficacy, academic pursuits [ 56 ], active coping skills [ 57 ], general mental health and career efficacy [ 58 ], academic outcomes [ 45 ], and future-planning style and career goal setting [ 59 ]. Similarly, mentees’ perceived high support from their mentors and low conflict within the mentoring relationship predicted a decrease in externalizing problems in a long-term mentoring program aimed at reducing aggressive behaviors [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentors’ rated support was also related to an increase in empathy, cooperation, self-control, assertiveness [ 49 ], social self-efficacy, and sense of community [ 50 ]. Mentees’ rated feelings of trust and closeness with their mentors were positively associated with an increase in social support and family bonding, scholastic competence, feelings of self-worth [ 18 , 51 , 52 , 53 , 54 ], self-regulation [ 55 ], hope, self-esteem, self-efficacy, academic pursuits [ 56 ], active coping skills [ 57 ], general mental health and career efficacy [ 58 ], academic outcomes [ 45 ], and future-planning style and career goal setting [ 59 ]. Similarly, mentees’ perceived high support from their mentors and low conflict within the mentoring relationship predicted a decrease in externalizing problems in a long-term mentoring program aimed at reducing aggressive behaviors [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although culture can affect the goals and practices of the relationship [ 156 ], researchers have rarely examined whether the characteristics of the mentoring relationship are universal or culturally dependent [ 157 , 158 ]. Indeed, studies internationally have underscored the widespread notion of mentoring as a warm, caring relationship (see, for example, studies in Hong Kong—Chan and Ho, [ 64 ]: China—Chan et al [ 58 ]; Glasgow—McArthur et al [ 56 , 159 ]; Rwanda—[ 60 ]; UK—[ 107 ]; Sweden—[ 39 ]; and the Czech Republic—[ 160 ], with only passing attention paid to the role played by race and ethnicity in formal mentoring relationships [ 161 , 162 , 163 , 164 , 165 ]. Furthermore, questions about whether formal mentors from different cultures provide different kinds of support and how their mentees perceive this support have rarely been addressed [ 117 , 164 , 165 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, well-designed health, mental health, and educational programs have facilitated the integration of migrant children into their new societies and reduced the effects of the multiple risk factors they experience (Chen, Wang, and Wang 2009;Connor et al 2007;Hamilton 2013a, b;Hannah 2007;Hjern et al 2013;Keung Ong et al 2009;Margari et al 2013;Oort et al 2007;Säävälä 2012;Wu et al 2012;Yao and Hao 2013). Several programs that adopted a more holistic approach and emphasized enhancing migrant children's self-efficacy (Chan et al 2011), social competence (Chen, Wang, and Wang 2009), empowerment (Hannah 2007), happiness (Jordan and Graham 2012), self-esteem (Peng et al 2012;Xiu-Yun et al 2009), and agency (Roddy 2012) are particularly noteworthy. The latter studies are closely related to the research reported in this article which focuses on the possession of hope among unaccompanied immigrant youth in family reunification programs within one agency's affiliate network.…”
Section: Risk Resiliency and Hope Among Migrant Childrenmentioning
confidence: 99%